PRAKTIKALITAS PENGGUNAAN MEDIA E-KOMIK PADA MATA PELAJARAN KEAMANAN PANGAN DI SMK NUSATAMA PADANG - Yelvia Prahagia; Maswati Maswati; Ratih Juwita Novalia (LP3M STKIP Muhammadiyah Muara Bungo, 2023)
This study aims to improve student learning outcomes in the subject of food safety through the development of e-comic media at SMK Nusatama Padang. This research is a development research with a 4-D model. The data in this study are the results of qualitative research given by experts/teachers and students through a given questionnaire. Then the daily test scores (UH) and practice scores. The results showed that: The use of e-comic learning media can improve student learning outcomes by looking at differences in learning outcomes from the pretest and posttest. Posttest learning outcomes are higher than the pretest. Therefore, e-comic media is recommended for use by teachers in teaching food safety.